Using the precaution adoption process model and the health belief model to understand radon testing and mitigation: a pre-post quasi-experimental study - Allison Maier; Erin Hayes; Lisa Munday (BMC, 2023)
Abstract Background Despite being the leading cause of lung cancer for non-smokers, few Canadians take action to test for and mitigate radon. This study's aim was twofold: (1) to investigate predictors of radon testing and mitigation using the Precaution Adoption Process Model (PAPM) and Health Belief Model (HBM); and (2) to assess the impact on beliefs of receiving radon results above health guidelines. Methods A convenience sample within Southeastern Ontario households was recruited to test their homes for radon (N = 1,566) for a pre-post quasi-experimental study. Prior to testing, participants were surveyed on risk factors and HBM constructs. All participants whose homes tested above the World Health Organization's radon guideline (N = 527) were surveyed after receiving their results and followed for up to 2 years after. Participants were classified into PAPM stages and regression analyses were conducted to determine predictors between different stages (from deciding to test onwards). Paired bivariate analyses compared responses before and after receiving results. Results Perceived benefits from mitigating was associated with progressing through all stages in the study's scope. Perceived susceptibility to and severity of illness and perceptions of cost and time to mitigate were associated with progression through some PAPM stages. Homes with smokers or individuals under 18 were associated with not progressing through some stages. Home radon level was associated with mitigation. Attitudes towards many HBM constructs significantly decreased after receiving a high radon result. Conclusions Public health interventions should target specific radon beliefs and stages to ensure households test and mitigate for radon.